Front Cover. Issue 1 (29th January 2020) - Ohlsson, Bodil; Dahlin, Lars B.; Englund, Elisabet; Veress, Béla
Abstract : The cover image is based on the Case Report Autonomic and peripheral neuropathy with reduced intraepidermal nerve fiber density can be observed in patients with gastrointestinal dysmotility by Bodil Ohlsson, Béla Veress, LARS B DAHLIN et al., https://doi.org/10.1002/ccr3.2575 .